Analyzing the complexity of animal products’ processing and its impact on sustainability - Germond, Arno; Fardet, Anthony; Álvarez García, Carlos; Boland, Mike; Ming Hoang, Hong; Mullen, Anne-Maria; Kaur, Lovedeep (Frontiers in Sustainable Food Systems, 2024)
Processing is an inevitable step in the manufacturing of animal-based foods (ABF) and animal byproducts (ABP). However, our society has reached a point where our food systems have reached unsustainable levels. The impact of ABF/ABP processing on sustainability has been arguably overlooked in comparison with production. This perspective paper aims to discuss and identify research gaps regarding the assessments of the sustainability of ABF/ABF processing. First, we describe why processing techniques can have various levels of complexity, with uses that are more or less impactful on the environment depending on the products and possible synergies. In the second part, we review how impacts on sustainability have been evaluated at global and local scales using life cycle assessments (LCA). To contribute to such an approach, we suggest novel or recently introduced types of indicators that would improve future LCA studies by capturing relevant information. In the third part, we encourage a systemic view of sustainability by considering the complexity of the whole supply chains of ABF and ABP. We highlight the current gaps or challenges in evaluating sustainability across supply chains and point the readers toward recent studies that address these limitations. We hope this perspective will help improve the design of academic and industrial studies or evaluation of ABF and ABP sustainability.